2020
DOI: 10.1371/journal.pone.0242773
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of autism genes to tissue-wide expression and dysfunction of synapse, calcium signalling and transcriptional regulation

Abstract: Autism Spectrum Disorder (ASD) is a heterogeneous disorder that is often accompanied with many co-morbidities. Recent genetic studies have identified various pathways from hundreds of candidate risk genes with varying levels of association to ASD. However, it is unknown which pathways are specific to the core symptoms or which are shared by the co-morbidities. We hypothesised that critical ASD candidates should appear widely across different scoring systems, and that comorbidity pathways should be constituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 132 publications
3
13
0
Order By: Relevance
“…In vivo, in vitro and ex vivo studies have shown that APAP directly perturbs hormone-dependent processes, including inhibition of androgen production and increased oestrogen production, disruption of steroidogenesis, depletion of sulfated sex hormones, perturbation of immune function, induction of oxidative stress and indirect activation of the endocannabinoid system 1,2,[61][62][63][64][65] . Independently of APAP, these processes have been implicated as mechanisms related to the development of neurodevelopmental [66][67][68][69][70][71][72][73][74][75][76] and reproductive disorders 2 . In addition to potential effects on neuronal and reproductive development, a combination of clinical studies together with experimental work in animal models and cell lines has also suggested that APAP exposure during pregnancy might decrease fetal haematopoietic stem cell numbers alter steroidogenesis in the placenta and induce placental damage 65,[77][78][79][80] .…”
Section: Nature Reviews | Endocrinologymentioning
confidence: 99%
“…In vivo, in vitro and ex vivo studies have shown that APAP directly perturbs hormone-dependent processes, including inhibition of androgen production and increased oestrogen production, disruption of steroidogenesis, depletion of sulfated sex hormones, perturbation of immune function, induction of oxidative stress and indirect activation of the endocannabinoid system 1,2,[61][62][63][64][65] . Independently of APAP, these processes have been implicated as mechanisms related to the development of neurodevelopmental [66][67][68][69][70][71][72][73][74][75][76] and reproductive disorders 2 . In addition to potential effects on neuronal and reproductive development, a combination of clinical studies together with experimental work in animal models and cell lines has also suggested that APAP exposure during pregnancy might decrease fetal haematopoietic stem cell numbers alter steroidogenesis in the placenta and induce placental damage 65,[77][78][79][80] .…”
Section: Nature Reviews | Endocrinologymentioning
confidence: 99%
“…33,34 However, we know that an altered connectivity is shared between the two and that many of the mutations related to these disorders converge on biological pathways involved in neuronal communication. Therefore, according to previous studies, 35 some of the main risk genes are clustered into three groups that could guide in the understanding of the epilepsy-ASD phenotype with respect to being a problem of connectivity: (a) ion channels, (b) synaptic function and structure, and (c) transcriptional regulators. Figure 3 shows genes classified by family of mechanisms for both ASD and epilepsy.…”
Section: Current Understanding Of the Genetic Basis Of Childhood Epilepsy And Comorbid Asdmentioning
confidence: 99%
“…WES studies have extended our in-depth knowledge on the rare de novo SNVs and CNVs impacting protein coding genes leading to dysregulation of signaling pathways controlling nervous system development, neuronal activity, synaptic homeostasis, immune response, chromatin modification, transcription and translation [ 9 , 10 , 11 , 12 ].…”
Section: Genetics Studiesmentioning
confidence: 99%
“…Autism etiology has many key players, including common genetic variants, inherited gene-disruptive mutations and rare variants of large effect outside of the coding region [ 6 , 7 , 8 ]. A number of pathways dysregulated in ASD, involve chromatin remodeling, RNA transcription and splicing, synaptic function, ion-channels, MAPK and calicium signaling [ 9 , 10 , 11 , 12 ]. This review will provide current information on innovative technologies like WES, WGS, non-coding RNAs, ASD models, pharmacogenomics and endophenotypes in ASD.…”
Section: Introductionmentioning
confidence: 99%